Implementasi Supervisi Akademik dalam Meningkatkan Kompetensi Guru Matematika di SMA Negeri 1 Tuntang - Rahmawati, Azizah; Adawiyah, Ainun; Umami, Mashlihatul (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to describe the process of implementing academic supervision in improving the pedagogical and professional competencies of mathematics teachers at SMA Negeri 1 Tuntang, with a focus on the planning, implementation, follow-up, and identification of appropriate supervision models. The research method used a descriptive qualitative approach with data triangulation, and data was collected through observation, interviews, and documentation. The results show that academic supervision is carried out twice a year through three stages, namely pre-supervision, supervision implementation, and post-supervision. The discussion reveals that supervision is carried out with contextual, nurturing, and effective assistance from senior teachers, which has a positive impact on the quality of student learning. Academic supervision at SMA Negeri 1 Tuntang effectively improves the competence of mathematics teachers through a senior teacher-based reflective model, with recommendations for increasing frequency, and integrating technology for more interactive and adaptive learning. The main obstacles include a busy schedule and excessive administrative focus, while collaborative supervision (between teachers or teachers and students) is not yet optimal.